PENGARUH FILM EDUKASI (DI TIMUR MATAHARI) TERHADAP NILAI KARAKTER NASIONALIS SISWA KELAS 5 SDN 053967 DURIAN LINGGA - Br Sinulingga, Adinda Carolita; Simanjuntak, Sorta; Lubis, Wildansyah; Simanungkalit, Erlinda; Afriadi, Putra (Jurnal Merah Putih Sekolah Dasar, 2024)
This research was carried out with the aim of finding out the significant value of the educational film (Di Timur Matahari) on the nationalist character values of grade 5 students at SDN 053967 Durian Lingga. The research method used in this research is a quasi-experimental research method. The design of this research is a pretest and posttest control group design. This research was carried out at SDN 053967 Durian Lingga which consisted of 2 classes, namely the experimental class (5A) and the control class (5B). Data collection techniques were carried out using observation, questionnaires and documentation. The instruments used were questionnaires to measure students' nationalist character values and also observations to observe students' nationalist character values. The collected data was analyzed statistically using the t-test.From the research results, it is known that the nationalist character score of experimental class students got an average score of 76.15 in the good category and the control class got an average score of 69.38 also in the good category. Furthermore, the value of tcount>ttable is 7.48>2.03 at a significance level of 5% or 0.05, meaning that Ha is accepted and Ho is rejected. This shows that there is a difference between the nationalist character values that use educational films (in the East of the Sun) and the nationalist character values without films. Thus, the use of educational films (in the east of the sun) has an effect in increasing the nationalist character values of grade 5 students at SDN 053967 Durian LinggaKeywords : Educational Films, Character Education, Nationalist Character Values.